An Extensive Analysis of the Significance and Difficulties of Microgrids Based on Renewable Energy in Wireless Sensor Networks - Hussain, Md. Naeem; Kader, Kazi Abdul; Ali, Md. Sumon; Ullah, Aman; Dodaev, Zohar Al (Control Systems and Optimization Letters, 2024)
The main objective of this paper is to review the importance of renewable energy based microgrid on wireless sensor networks (WSNs) including challenges of renewable energy-based MGs. This paper explores the critical nexus between Wireless Sensor Networks (WSNs) and microgrids powered by renewable energy, explaining the rising importance of these networks and the issues they provide. Microgrids have become a promising technology in the worldwide search for sustainable energy solutions, since they allow for the effective integration of distributed energy management, local energy production, and Renewable Energy (RE) sources. WSNs allow for the microgrid-wide real-time monitoring of multiple parameters, including voltage, current, temperature, and humidity. The constant flow of data contributes to the preservation of ideal operating circumstances. When combined with WSNs' powers to enable data-driven decision-making and real-time monitoring, these two technologies have the potential to revolutionize a wide range of applications. This paper offers a thorough examination of the significance of this synergy, including topics like environmental effect mitigation, grid resilience, and energy sustainability. In addition, the study analyzes the complex issues related to energy management, communication protocols, security, scalability, and integration with intermittent renewable sources that arise when synchronizing microgrids with WSNs. Future directions and new trends are also examined, including the growth of Internet of Things and AI-driven energy optimization. This study intends to assist academics, policymakers, and practitioners in realizing the full potential of microgrid implementations based on renewable energy for a more sustainable and interconnected future by illuminating the symbiotic link between microgrids and WSNs.